Characterization and stability for Cottonwood riverbank-a reliability study for BSTEM - Lu, Wenqian (Kansas State University, 2022)
Riverbank slope failure due to excessive rainfall and flooding can be costly; however, riverbank slopes may also fail due to upstream engineering structures as an unintended consequence. Many methods and models can be used for slope stability analysis to evaluate how upstream engineered structures impact downstream riverbanks. The objective of this study is to determine an efficient implementation of soil properties for the Bank Stability and Toe Erosion Model (BSTEM), which is commonly used for riverbank stability analysis in Kansas. The stability of a bank along the Cottonwood River in Kansas was evaluated using soil properties obtained from various complex test methods. Soil properties were determined from the consolidated undrained and unconsolidated undrained triaxial tests. Correlations based on the soil type, BSTEM default soil data, and empirical correlations based on measured soil properties were also used to obtain the required BSTEM soil properties. The results of this study indicate that the soil properties obtained from an effective stress analysis, as required by BSTEM, using the consolidated undrained triaxial test provide the most accurate factor of safety. Soil properties obtained using total stress analysis and based on soil classification led to more conservative, yet reasonable factors of safety. The use of numerically-correlated soil properties was not appropriate, nor were some built-in soil properties within BSTEM. Thus, while BSTEM calls for effective stress parameters, a slightly more conservative and more simplified analysis can be conducted using either measured total stress parameters, or mean values based on soil classification. Ultimately, researchers must evaluate the appropriate risk when selecting the type of data to use for evaluating riverbank stability using BSTEM. This study recommends that BSTEM include an option for total stress analysis for future model development to represent a more critical failure case and to be more conservative.
Keywords: Slope stability; BSTEM; Triaxial test; Clay